2017
DOI: 10.1002/hyp.11161
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the importance of seepage and springs to nitrate flux in a stream network in the Wisconsin sand plains

Abstract: Evaluating the flow paths that contribute to solute flux in stream networks can lead to greater understanding of the linkages between biogeochemistry and hydrology. We compared the contributions of groundwater in spring brooks and in seepage through the streambed to nitrate flux in the Emmons Creek network in the Wisconsin sand plains. We predicted that spring brooks would contribute disproportionately to nitrate flux due to the presumed higher advection rates in springs and less opportunity for nitrate remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
5
2
Order By: Relevance
“…Riparian seeps supply 45–217 m 3 /d of water and 0.6–4.2 kg/d of N. Comparatively, 0.8–13.2 m 3 /d of water and 0.02–0.25 kg/d of N are lost to groundwater. These results differ from work by Stelzer et al (2017) working in the sand plains of Wisconsin, where 37% of streamflow was derived from preferential flow in spring brooks (which were defined as outflows from riparian springs, similar to our definition of seeps), and 63% was made up of streambed groundwater matrix flow. Despite being in an agricultural watershed, nitrate concentrations were considerably lower in their study stream, approximately 2.5 mg N L −1 , and the stream reach was approximately 10 times longer, 1450 m. Differences in the ecoregion and underlying geology of the two sites also would affect groundwater flow paths, as the stream studied by Stelzer et al (2017) was underlain by an unconfined aquifer of well‐sorted sands whereas the site studied here is situated on fractured bedrock.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Riparian seeps supply 45–217 m 3 /d of water and 0.6–4.2 kg/d of N. Comparatively, 0.8–13.2 m 3 /d of water and 0.02–0.25 kg/d of N are lost to groundwater. These results differ from work by Stelzer et al (2017) working in the sand plains of Wisconsin, where 37% of streamflow was derived from preferential flow in spring brooks (which were defined as outflows from riparian springs, similar to our definition of seeps), and 63% was made up of streambed groundwater matrix flow. Despite being in an agricultural watershed, nitrate concentrations were considerably lower in their study stream, approximately 2.5 mg N L −1 , and the stream reach was approximately 10 times longer, 1450 m. Differences in the ecoregion and underlying geology of the two sites also would affect groundwater flow paths, as the stream studied by Stelzer et al (2017) was underlain by an unconfined aquifer of well‐sorted sands whereas the site studied here is situated on fractured bedrock.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, the highly fractured nature of the shale bedrock underlying RS can facilitate larger amounts of preferential flow, while the low hydraulic conductivities of the streambed generally hinder matrix flow. Hydraulic conductivities reported by Stelzer et al (2017) ranged from 1.7 to 8.64 m/d, while this study found hydraulic conductivities ranging from 0.0009 to 8.27 m/d, with 7 of 14 measurements <1 m/d.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Because M b accounted for most of the variation in F med 200 in the final predictive model, the primary mechanism of transient storage in Spring Coulee Creek was surface storage presumably caused by macrophyte beds. Others have likewise concluded that sand‐bed streams have very little hyporheic storage (Harvey & Wagner, ; Jin & Ward, ; Stelzer, Strauss, & Coulibaly, ; Stofleth et al, ). Values of A s / A in Spring Coulee Creek (0.15 ± 0.07) were similar to what Powers et al () found in other Wisconsin streams and were within range of the mean for sand‐bed streams (0.36 ± 0.22, as reviewed by Stofleth et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Percolation is the seepage of soil water out of the root zone and usually regarded as the water flux moving downward from the bottom of the root zone (Hare et al, 2017; Stelzer et al, 2017). Percolation is an important link in the water cycle (Xie et al, 2015) and water balance processes, especially for groundwater resources (Min et al, 2018).…”
Section: Introductionmentioning
confidence: 99%